Investigation of the neutron halo of the 11Be nucleus - Valiolda, D.S.; Janseitov, D.M.; Zhaugasheva, S.A.; Zhussupova, N.K. (Recent Contributions to Physics, 2018)
Exotic nuclei are the subject of intensive experimental research. Coulomb breakup are relevant for interpretation and planning of experiments in radioactive beams. These investigations have opened new prospects in studying the structure of nucleus and have found applications in other areas of physics, including nuclear astrophysics. The halo is one of the most intensively studied objects in modern low-nucleus physics. The mean radii of certain nucleons orbits may be larger than nuclear interaction range. A characteristic feature of halo nuclei physics is correlations between the mechanism of nuclear reaction and structure. The breakup is one of the important tools for studying halo properties. In these reactions, the information from dissociation of projectile into fragments could be used to conclude about the properties of halo part wave function. With a good approximation, the breakup could be regarded as a transition from the bound state of two (three) particles to the continuum, due to the changing Coulomb field. This paper is devoted to a theoretical study of the Coulomb breakup of halo nuclei in a quantum approach. The energy levels of the halo of the 11Be nucleus are calculated, taking into account the influence of an external magnetic field, i.e. the splitting of energy levels by numerical and analytical methods using two different potentials is calculated: in the form of Woods-Saxon and Gauss. The 11Be nucleus is regarded as a neutron halo consisting of 10Be core and one neutron. The root mean square charge radius of the 11Be nucleus in the ground state is also calculated numerically. This work is the initial stage of the work on the investigation of the breakup of halo nuclei in the quantum-mechanical approach.